2006
DOI: 10.1007/s00424-006-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

P2 receptors and neuronal injury

Abstract: Extracellular adenosine 5'-triphosphate (ATP) was proposed to be an activity-dependent signaling molecule that regulates glia-glia and glia-neuron communications. ATP is a neurotransmitter of its own right and, in addition, a cotransmitter of other classical transmitters such as glutamate or GABA. The effects of ATP are mediated by two receptor families belonging either to the P2X (ligand-gated cationic channels) or P2Y (G protein-coupled receptors) types. P2X receptors are responsible for rapid synaptic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 339 publications
(428 reference statements)
1
122
0
3
Order By: Relevance
“…We have recently found that the blockade of this receptor affords a robust neuroprotection against damage of hippocampal neurons in different models of excitotoxicity (unpublished results) in agreement with the neuroprotection afforded by P2Y receptor antagonists in in vivo models of ischemia (Franke et al, 2006). We now found that the density of presynaptic hippocampal P2Y1 receptors is similar (P > 0.05) in all age groups tested (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We have recently found that the blockade of this receptor affords a robust neuroprotection against damage of hippocampal neurons in different models of excitotoxicity (unpublished results) in agreement with the neuroprotection afforded by P2Y receptor antagonists in in vivo models of ischemia (Franke et al, 2006). We now found that the density of presynaptic hippocampal P2Y1 receptors is similar (P > 0.05) in all age groups tested (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Thus, drugs activating presynaptic modulators such as adenosine A 1 receptors (Fredholm et al, 2005) or cannabinoid CB 1 receptors (van der Stelt and Di Marzo, 2005) might afford protection against different neurodegenerative diseases. Also, antagonists of adenosine A 2A receptors (Fredholm et al, 2005), metabotropic group 5 receptors (Flor et al, 2002) or ATP P2Y1 receptors (Franke et al, 2006) also confer neu-roprotection in different animal models of brain degenerative diseases. However, the study of novel neuroprotective strategies has mostly been carried out using young adult animals, whereas most neurodegenerative diseases are prevalent in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore characterized Ca 2ϩ responses to several stimulators and inhibitors of endogenous GPCRs on the primary cultured esophageal enteric neurons. Broadly, purinergic receptors are divided into two groups: ligand-gated ion channels (P2X) and GPCRs (P2Y) (17). Several subtypes of purinergic receptors respond to ATP with increases in [Ca 2ϩ ] cyt (41).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, adenosine concentrations were below detection in culture medium harvested from C6 -Cx43 Ϫ cells (data not shown). Given that C6 -Cx43 ϩ cells express both P1 and P2 purinergic receptors, ATP has the potential to activate multiple types of receptors, known to modulate the cellular injury resistance (Brismar, 1995;Abbracchio and Verderio, 2006;Franke et al, 2006;Kobayashi et al, 2006). To evaluate the relative impact of purinergic receptors on the resistance of C6 -Cx43 ϩ cells after preconditioning, we compared the effect of several P 1 or P 2 receptor antagonists.…”
Section: Adenosine Mediates Injury Resistance After Preconditioningmentioning
confidence: 99%